Economic Analysis of Benefits and Costs: Multiple Uses Water Services Project supported by the Challenge Programme on Water and Food - Jumbe, C.B.L.; Chinangwa, S.M.J. (FANRPAN, 2008)
The Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) contracted the Center for Agriculture Research and Development (CARD) to undertake the economic analysis of the benefits and costs of the MUS Project with the principal aim of drawing lessons from the project’s experience with regard to achieving developmental impacts through research as well as providing basis for addressing “efficiency and effectiveness” questions of multiple-use approaches over single-use approaches. The analysis was conducted at the request of the Challenge Program on Water and Food (CPWF) “CPWF Adoption and Cost-Benefit Analysis Project” against the background that the MUS Project, implemented in eight countries since 2004, had identified considerable change/impact at local, national and even global levels in terms of adoption of the concept of supplying water to meet multiple needs. The analysis of benefits and costs in this report was meant to build on the Winrock study whose analysis centered on the incremental benefits, poverty impacts and costs of multiple use approaches relative to single use approaches. While the Winrock study provided useful and important information and guided the identification of benefits and costs of the MUS Project, the analysis in this report also uses the technical approach for evaluating research and advocay projects. The use of the latter approach is due to data limitations as a result of the research nature of the MUS Project. The analysis focuses on the extent of influence the MUS Project appeared to have had on the changes/impacts observed in the basins/countries rather than whether the MUS Project directly produced the observed results. The analysis merely relates the MUS Project activities with the results reported in the five basins by examining the benefits that have accrued or are likely to accrue in the future that would not have happened without the CPWF project investment support.